Sleep medication and melatonin use among Norwegian nurses - A cross‐sectional study - Ingeborg Forthun; Siri Waage; Ståle Pallesen; Bente Elisabeth Moen; Bjørn Bjorvatn (Wiley, 2022)
Abstract Aim To estimate the prevalence of sleep medication and melatonin use among nurses and to assess if factors related to work, sleep or mental health, were associated with such use. Design A cross‐sectional study. Methods A questionnaire survey including 2,798 Norwegian nurses. Associations were estimated using a modified Poisson regression model. Results In total, 7.5%, 4.6% and 2.0% of the nurses included in the present study reported prescribed sleep medication, over‐the‐counter sleep medication or melatonin use in the last year, respectively. Short sleep duration, sleep problems and psychological conditions were strongly associated with both prescribed and over‐the‐counter sleep medication use. Nurses who worked more than 60 night shifts in the last year were at increased risk of sleep medication use.